A Reverse Design Method for Convective PCR Chips Featuring Precise Control of Steady-State Flow Fields - Chenfei Li; Yaping Xie; Haochen Yong; Xin Zhao; Xingxing Ke; Zhigang Wu (Chemosensors)
Convective Polymerase Chain Reaction (cPCR), owing to its enhanced thermal cycling efficiency, holds promise for application in the next generation of mainstream commercial PCR instruments. Despite its potential, existing capillary-based and annular reaction chamber designs encounter limitations in precisely controlling the internal flow field, which poses a significant barrier to the progression of cPCR. To overcome these obstacles, this work innovatively proposes a cPCR chip utilizing a “racetrack-shaped” reaction chamber, along with a reverse design approach tailored to meet diverse reaction requirements. Through modeling and simulation, we accurately obtained the relationship between the design parameters and the average flow velocity of the cPCR chip with a “racetrack-shaped” reaction chamber. By capturing the motion of fluorescent particles using a high-speed camera, we acquired the velocity distribution of the actual flow field. Further, we utilized these relationships to conduct a reverse design. Ultimately, a reaction chamber was designed based on the actual amplification needs of 2019-nCoV and hepatitis B virus, and successful amplification was achieved using a self-developed temperature control platform.